PERAN PERPUSTAKAAN MASJID BAITURRAHMAN BALAI PANJANG SUMATERA BARAT DALAM TRADISI “KEMBALI KE SURAU” - Fadhila Nurul Husna Zalmi; Dian Hasfera; Arifah Yenni Gustia (UIN Imam Bonjol Padang, 2019)
The library of the Baiturrahman Mosque in Balai Panjang, West Sumatra, is a place for the surrounding community to search for information and exchange information and learn in the fields of religion, social and culture. The collection is used to discuss and dialogue in sharing knowledge through several activities in